Advances in Cephalometry in Relation to the Shift in Soft Tissue Paradigm for Orthodontic Treatment Planning - Rashmita Sahoo1 , Nihar Ranjan Sahoo2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
The discovery of imaging and its use in orthodontics is a subject of technology describing biology.Developments in arch-wires,brackets and composites changed the mechanics of orthodontic treatment. Thedevelopments in imaging technology have changed the perception of the clinician as well as the patienttowards esthetics. The newer imaging technology helps to study the craniofacial growth pattern of youngerpatients and to know the effect of orthodontic treatment on this dynamicprocess of growth. Earlier, in 20thcentury, 2-dimensional (2D) radiography was used,but in 21st century, the new 3-dimensional (3D) scannersuse less ionizing radiation and give more information than conventional radiographs. This article is areview of the imaging technology used in orthodontic diagnosis and treatment planning from the use of thecephalostat to the introduction of cheap,reduced radiation Cone Beam imaging of 3D cephalograms.